Analysis based on the diffusion model for saturation silica gel with water vapor at conservation units steam circuit TPP; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 82 : Thermophysical Basis of Energy Technologies - Goldaev S. V. Sergey Vasilievich (2015, 2015)
Title screen